Formulation And Evaluation of plant-based Hydrogel for Antimicrobial Activity - Sahu, Shweta; Dubey, Vishal; Tiwari, Megha; Pal, Ritik; Deepika, Km; Gupta, Sneha; Sahu, Sachin (Journal of Neonatal Surgery, 2025)
The study was aimed to develop and evaluate a plant-based hydrogel incorporating chitosan polymer for its in-vitro antibacterial activity. The hydrogel was prepared by using chitosan polymer, methyl paraben, propyl paraben, glycerin, acetic acid, triethanolamine, moringa oleifera leaf extract and distilled water. Triethanolamine was gradually added drop by drop to maintain the pH of skin. The hydrogel formulations were assessed based on various parameters, including physical appearance, homogeneity, viscosity, extrudability, pH, spreadability, moisture content and antimicrobial efficacy. The formulated gel was dark brown, homogenous and pH ranges from 6.24 to 6.29 which is close to the skin pH. Formulation F4 showed acceptable rheological property with applicable spreadability, extrudability, moisture content and in- vitro antibacterial activity. The phytochemical screening of methanolic extract revealed the presence of various secondary metabolites such as flavonoids, alkaloids, glycosides, terpenoids, saponins, phenols and tannins. Antimicrobial activity was tested using the agar well diffusion method. The m. oleifera plant was recognized as a rich source of natural antimicrobial agents due to its phytochemical properties. The antimicrobial activity of the test sample was quantified by measuring the diameter of the inhibition zone in millimeters. The formulation F4 shows highest inhibition zone of 17mm at the highest concentration (100mg/ml). Antimicrobial screening revealed that the crude methanolic extract exhibited antimicrobial activity against Staphylococcus epidermidis